The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.2984/049.063.0204
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Density, and Biomass of Introduced Small Mammals in the Southern Mariana Islands

Abstract: Although it is generally accepted that introduced small mammals have detrimental effects on island ecology, our understanding of these effects is frequently limited by incomplete knowledge of small mammal distribution, density, and biomass. Such information is especially critical in the Mariana Islands, where small mammal density is inversely related to effectiveness of Brown Tree Snake (Boiga irregularis) control tools, such as mouse-attractant traps. We used mark-recapture sampling to determine introduced sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…Several species of civets ( Viverridae), which are nocturnal mammals, are predators of R. rattus in the Philippines (Rickart et al 1993). Monitor lizards (Varanus indicus) and the brown tree snake (Boiga irregularis) are predators of R. rattus in the Mariana Islands ( Wiewel et al 2009) …”
Section: Natural Enemiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several species of civets ( Viverridae), which are nocturnal mammals, are predators of R. rattus in the Philippines (Rickart et al 1993). Monitor lizards (Varanus indicus) and the brown tree snake (Boiga irregularis) are predators of R. rattus in the Mariana Islands ( Wiewel et al 2009) …”
Section: Natural Enemiesmentioning
confidence: 99%
“…Phylogenetic restructuring of the "R. rattus complex" (Oceanic and Asian groups) continues to progress, and based on molecular evidence there are almost certainly multiple species within what has historically been identified as Rattus rattus (e.g., five to seven species in the R. rattus complex described by Robins et al [2007] and Pagès et al [2010], respectively). In the Mariana Islands, Wiewel et al (2009) reported that all species in their sampling that had been previously believed to be R. rattus or R. tanezumi were most closely related to the R. diardii group described by Robins et al (2007). Without molecular analysis of individuals within the R. rattus complex, it is very difficult to separate the species, and R. rattus and R. tanezumi are almost impossible to distinguish morphologically .…”
mentioning
confidence: 99%
“…Thus, of the three rat species we studied, the roof rat is probably the most arboreal, which is in line with our findings. Unfortunately, recent surveys raise the possibility that the roof rat (or the closely related R. diardii [ Wiewel et al 2009]) may be by far the most common of the three rat species on Guam (Wiewel et al 2009). The Polynesian rat is probably more arboreal than the Norway rat, but this was not evident in our study.…”
Section: Methodsmentioning
confidence: 99%
“…The necessity of obtaining confident estimates of numbers of snakes removed creates concern when other nonnative invasives, particularly Rattus spp., may be removing baits. At least three rat species have been documented on Guam: the roof rat, Rattus rattus (L.); Norway rat, Rattus norvegicus (Berkenhout); and Polynesian rat, Rattus exulans (Peale) (Baker 1946, Crabb and Emik 1946, Barbehenn 1974, Savidge 1987, although good estimates of current density are available only for R. rattus (Rattus diardii [ Wiewel et al 2009]; taxonomy sensu Robins et al [2007]). No information is available on propensities of these species to take DNM baits.…”
mentioning
confidence: 99%
“…The consequent loss of avian ecosystem function has resulted in cascading ecological consequences, including disturbance of plant reproduction (Mortensen et al 2008;Rogers 2011), forest regeneration (Perry and Morton 1999), and arthropod release (Rogers et al 2012). Predation by brown tree snakes has also negatively impacted nearly all native vertebrate populations on Guam as well as nonnative and domestic animals (Fritts and McCoid 1991;Wiewel et al 2009). …”
Section: Invasion and Impactsmentioning
confidence: 99%